Efeito do treinamento físico aeróbio no inotropismo miocárdico de ratos idosos - Yoshizaki, Amanda Pereira [UNIFESP] (2019)
Exercise training effects on the contractility of aged myocardium have been investigated for more than 20 years, but the data are still unclear. This study evaluated the hypothesis that a swimming training (ST) may improve myocardial inotropism in older rats. Male Wistar rats aged 4 (young) and 21 (old) months-old were divided into young untrained (YNT), old untrained (ONT), and old trained (OTR; 6 weeks of ST) groups. Echocardiography and hemodynamic were employed to assess left ventricular morphology and function. Myocardial mechanics was evaluated on papillary muscles. Histological and immunoblotting were carried out to evaluate fibrosis and proteins that modulate the myocardial function and calcium handling. We found that older rats did not show cardiac dysfunction, but ONT group showed lower physical performance during a swimming test (YNT: 5 ± 2; ONT: −16 ± 0.4; OTR: 51 ± 3; Δ%, sec). Moreover, ONT group showed worse myocardial inotropism, in which it was reversed by ST (Peak developed tension: YNT: 6.2 ± 0.7; ONT: 3.9 ± 0.3; OTR: 6.9 ± 0.9; g/mm2). The ST was associated with preserved collagen content (YNT: 0.38 ± 0.05; ONT: 0.78 ± 0.12; OTR: 0.34 ± 0.09; %). Exercise partially mitigated the effects of aging on intracellular Ca2+-regulating protein (eg, L-Ca2+ channel and phospholamban) and β-isoform of myosin. Thus, we propose that these molecular alterations together with inhibition of collagen increase contribute to improved myocardial performance in older rats.